Rapid size-focusing of gold nanoclusters with an oxidant - Kumaran, Elumalai (2020)
Rapid size-focusing of gold nanoclusters can be achieved by the addition of K3[Fe(CN)]6. The conditions for this have been optimized, and the possible role that it plays proposed.